Relationship between the Effects of Stress Induced by Human Bile Juice and Acid Treatment in Vibrio cholerae - Álvarez, Genoveva; Heredia, Norma; García, Santos (International Association for Food Protection, 2003)
The effects of low pH and human bile juice on Vibrio cholerae were investigated. A mild stress condition (exposure to acid shock at pH 5.5 or exposure to 3 mg of bile per ml for 20 min) slightly decreased (by #1 log unit) V. cholerae cell viability. However, these treatments induced tolerance to subsequent exposures to more severe stress. In the O1 strain, four proteins were induced in response to acid shock (ca. 101, 94, 90, and 75 kDa), whereas only one protein (ca. 101 kDa) was induced in response to acid shock in the O139 strain. Eleven proteins were induced in response to bile shock in the O1 strain (ca. 106, 103, 101, 96, 88, 86, 84, 80, 66, 56, and 46 kDa), whereas only one protein was induced in response to bile shock in the O139 strain (ca. 88 kDa). V. cholerae O1 and O139 cells that had been preexposed to mild acid shock were twofold more resistant to pH 4.5 (with times required to inactivate 90% of the cell population [D-values] of 59 to 73 min) than were control cells (with D-values of 24 to 27 min). Likewise, cells that were preexposed to mild bile shock (3 mg/ml) were almost twofold more tolerant of severe bile shock (30 mg/ml; D-values, 68 to 87 min) than were control cells (with D-values of 37 to 43 min). These protective effects persisted for at least 1 h after the initial shock but were abolished when chloramphenicol was added to the culture during the shock. Cells preexposed to acid shock exhibited cross-protection against subsequent bile shock. However, cells preexposed to bile shock exhibited no changes in acid tolerance.Bile shock induced a modest reduction (0 to 20%) in enterotoxin production in V. cholerae, whereas acid shock had no effect on enterotoxin levels. Adaptation to acid and bile juice and protection against bile shock in response to preexposure to acid shock would be predicted to enhance the survival of V. cholerae in hosts and in foods. Thus, these adaptations may play an important role in the development of cholera disease.